PENEREPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII4 SMP BABUSSALAM PEKANBARU - Wenni Astuti Astuti; Putri Yuanita Yuanita; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstarct: This research is a action research with the objective to fix the learning process and to improve student’s mathematicsproblem solving capabilities by applying Problem based learning Model. The subject of this research are the students at class VIII4 SMPBabussalam Pekanbaru at the second semester of academic years 2014/2015, which amounted to 25 students, consists of female students with heterogeneous level of academic capabilities. This research consists of 2 cycles, of which each cycle in composed of 4 stages, which is planning, implementation, observation and reflection. In every before a cycle pretest will be implemented and end of a cycle, posttest will be implemented. Data collection is done by observation and tests are mathematics problem solving . Data analysis is done by narrative descriptive and statistic descriptive analysis. The result from the observation page shows that (1) teacher-student activities had performed well after action has been made. Most of the students have participated actively in the learning process that has been exercised, such as step-by-step learning, presenting student worksheets about problem solving or question papers, responding a fellow classmate’s presentation, and giving learning conclusions. Students even try to resolve questions that the teacher has given correctly by the end of the learning process. (2) student mathematics problem solving capabilities increase had implemented problem based learning. The result of this research shows that the Problem Based Learning is capable of fixing the learning process and increasing math problem solving capabilities from the students at class VIII4 SMP Babussalam Pekanbaru at the second semester of academic years 2014/2015. Key words: Mathematics problem solving capabilities, Problem based learning